Stent-Screw Assisted Internal Fixation of Osteoporotic Vertebrae: A Comparative Finite Element Analysis on SAIF Technique - La Barbera, Luigi; Cianfoni, Alessandro; Ferrari, Andrea; Distefano, Daniela; Bonaldi, Giuseppe; Villa, Tomaso (Frontiers in Bioengineering and Biotechnology, 2019)
Vertebral compression fractures are one of the most relevant clinical consequences caused by osteoporosis: one of the most common treatment for such fractures is vertebral augmentation through minimally invasive approaches (vertebroplasty or balloon-kyphoplasty). Unfortunately, these techniques still present drawbacks, such as re-fractures of the treated vertebral body with subsidence of the non-augmented portions or re-fracture of the non-augmented middle column at the junction with the augmented anterior column. A novel minimally-invasive augmentation technique, called Stent-Screw Assisted Internal Fixation, has been recently proposed for the treatment of severe osteoporotic and neoplastic fractures: this technique uses two vertebral body stents and percutaneous cannulated and fenestrated pedicular screws, through which cement is injected inside the expanded stents to achieve optimal stents’ and vertebral body’s filling. The role of the pedicle screws is to anchor the stents-cement complex to the posterior column, acting as a bridge across the middle column and preserving its integrity from possible collapse. In order to evaluate the potential of the new technique in restoring the load bearing capacity of the anterior and middle spinal columns and in reducing bone strains, a Finite Element model of an osteoporotic lumbar spine has been developed. Both standard vertebroplasty and Stent-Screw Assisted Internal Fixation have been simulated: simulations have been run taking into account everyday activities (standing and flexion) and comparison between the two techniques, in terms of strain distribution on vertebral endplates and posterior and anterior wall, was performed. Results show that Stent-Screw Assisted Internal Fixation significantly decrease the strain distribution on the superior EP and the cortical wall compared to vertebroplasty, possibly reducing the re-fracture risk of the middle-column at the treated level.